The anti-angiogenic herbal extract from Melissa officinalis inhibits adipogenesis in 3T3-L1 adipocytes and suppresses adipocyte hypertrophy in high fat diet-induced obese C57BL/6J mice. (3rd February 2016) - Woo, Sangee; Yoon, Miso; Kim, Jeongjun; Hong, Yeonhee; Kim, Min-Young; Shin, Soon Shik; Yoon, Michung
Abstract: Ethnopharmacological relevance: Melissa officinalis L. (Labiatae; lemon balm) has been used traditionally and contemporarily as an anti-stress herb. Current hypotheses suggest that not only chronic stress promotes angiogenesis, but angiogenesis also modulates adipogenesis and obesity. Because the herbal extract ALS-L1023 from M. officinalis L. (Labiatae; lemon balm) has an anti-angiogenic activity, we hypothesized that ALS-L1023 could inhibit adipogenesis and adipocyte hypertrophy. Materials and methods: ALS-L1023 was prepared by a two-step organic solvent fractionation from M. officinalis . The effects of ALS-L1023 on adipogenesis in 3T3-L1 adipocytes and adipocyte hypertrophy in high fat diet (HFD)-fed obese mice were measured using in vivo and in vitro approaches. Results: ALS-L1023 inhibited angiogenesis in a dose-dependent manner in the HUVEC tube formation assay in vitro . Treatment of cells with ALS-L1023 inhibited lipid accumulation and adipocyte-specific gene expression caused by troglitazone or MDI differentiation mix. ALS-L1023 reduced mRNA expression of angiogenic factors (VEGF-A and FGF-2) and MMPs (MMP-2 and MMP-9) in differentiated cells. In contrast, mRNA levels of angiogenic inhibitors (TSP-1, TIMP-1, and TIMP-2) increased. Protease activity, as measured by zymography, showed that activity of MMP-2 and MMP-9 decreased in ALS-L1023-treated cells. ALS-L1023 also inhibited MMP-2 and MMP-9 reporter gene expression in the presence of the MMP inducer phorbol 12-myristate 13-acetate. An in vivo study showed that ALS-L1023 not only decreased adipose tissue mass and adipocyte size, but also reduced mRNA levels of adipose tissue angiogenic factors and MMPs in HFD-fed obese mice. Conclusions: These results suggest that the anti-angiogenic herbal extract ALS-L1023 suppresses adipogenesis and adipocyte hypertrophy, and this effect may be mediated by inhibiting angiogenesis and MMP activities. Thus, by curbing adipogenesis, anti-angiogenic ALS-L1023 yields a possible therapeutic choice for the prevention and treatment of human obesity and its associated conditions. Graphical abstract: